C-peptide is a predictor of telomere shortening: A five-year longitudinal study - Racha Ghoussaini; Hani Tamim; Hani Tamim; Hani Tamim; Martine Elbejjani; Martine Elbejjani; Maha Makki; Lara Nasreddine; Lara Nasreddine; Hussain Ismaeel; Hussain Ismaeel; Mona P. Nasrallah; et al. (Frontiers in Endocrinology, 2022)
AimRelative telomere length (RTL) predicts the development of many age-related diseases. Yet, few studies have evaluated their longitudinal effect on RTL. We investigated longitudinally the association between cardiometabolic risk factors and RTL.MethodsThis was a longitudinal study with a 5-year follow-up period, based on data collected in 2014 and 2019. Of 478 participants in 2014, 198 consented to be followed-up in 2019. The associations between RTL and risk factors were analyzed using t-test, ANOVA or simple linear regression as applicable.ResultsRTL was significantly shortened after 5 years (P<0.001). Older age (P=0.018) and gender (P=0.05) were significantly associated with shorter RTL at follow-up. Higher baseline C-peptide correlated with shorter RTL (P=0.04) and shortening of RTL (P=0.03) after 5 years. Multivariate linear regression including both age and gender revealed a significant trend for C-peptide and change in RTL after 5 years (P=0.04). Interestingly, there was a trend of shorter RTL at follow-up with diabetes, though the findings were not statistically significant.ConclusionsHigher C-peptide level contributes to telomere shortening over time, suggesting that metabolic dysregulation may play a role in early aging. Further understanding of this relationship and addressing high C-peptide levels can be important to prevent premature aging.